Analisis Gender atas Pemenuhan Kebutuhan Biologis Suami dalam Kitab Qurratu al-‘Uyūn (Relevansi dan Kontekstualisasi dalam Rumah Tangga Kontemporer) - Hasan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Fulfilling biological needs in married life is an important aspect that contributes to the harmony and sustainability of marriage. This article aims to examine the fulfillment of a husband's biological needs from the perspective of the book Qurratu al-'Uyūn, known as one of the classic Islamic literatures that discusses the ethics and etiquette of husband-wife relations. The method used is library research with a descriptive-analytical approach to the contents of the book and its relevance to the context of modern life. The results of the study indicate that Qurratu al-'Uyūn places the husband's biological needs as a right that must be fulfilled by the wife, as long as there are no obstacles according to sharia. However, this fulfillment is not unilateral, but must be based on the principles of tenderness, attention, and a balance of rights and obligations between both partners. This book also emphasizes the importance of etiquette in biological relationships, such as good communication, foreplay (muqaddimah), and maintaining the psychological well-being of the couple. In the current context, the values ​​contained in the book remain relevant, especially in building relationships based on mutual understanding and respect. Thus, fulfilling biological needs is not only understood as a physical obligation, but also as part of worship that strengthens emotional and spiritual bonds in the household